Functional oral nanoparticles for delivering silibinin and cryptotanshinone against breast cancer lung metastasis - Ying Liu; Xingmei Xie; Xuefeng Hou; Junyi Shen; Jiangpei Shi; Haizhen Chen; Yuanzhi He; Zhi Wang; Nianping Feng (Journal of Nanobiotechnology, 2020)
Abstract Background Breast cancer lung metastasis occurs in more than 60% of all patients with breast cancer, and most of those afflicted by it eventually die of recurrence. The tumor microenvironment plays vital roles in metastasis. Modulating the tumor microenvironment via multiple pathways could efficiently prevent or inhibit lung metastasis. Silibinin and cryptotanshinone are natural plant products that demonstrate anti-metastasis effects and modulate the tumor microenvironment via different pathways. However, they have poor aqueous solubility, membrane permeability, and oral bioavailability. Oral drug administration may help improve the quality of life and compliance of patients with breast cancer, primarily under long-term and/or follow-up therapy. Herein, we developed poly-N-(2-hydroxypropyl) methacrylamide (pHPMA)-coated wheat germ agglutinin-modified lipid-polymer hybrid nanoparticles, co-loaded with silibinin and cryptotanshinone (S/C-pW-LPNs). We assessed their oral bioavailability, and evaluated their anti-metastasis efficacy in a 4T1 breast cancer tumor-bearing nude mouse model. Results An in vitro mucus diffusion study revealed that pHPMA enhanced W-LPN mucus penetration. After oral administration, pHPMA enhanced nanoparticle distribution in rat jejunum and substantially augmented oral bioavailability. S/C-W-LPNs markedly increased 4T1 cell toxicity and inhibited cell invasion and migration. Compared to LPNs loaded with either silibinin or cryptotanshinone alone, S/C-pW-LPNs dramatically slowed tumor progression in 4T1 tumor-bearing nude mice. S/C-pW-LPNs presented with the most robust anti-metastasis activity on smooth lung surfaces and mitigated lung metastasis foci. They also downregulated tumor microenvironment biomarkers such as CD31, TGF-β1, and MMP-9 that promote metastasis. Conclusions Silibinin- and cryptotanshinone-co-loaded pW-LPNs efficiently penetrate intestinal barriers, thereby enhancing the oral bioavailability of the drug loads. These nanoparticles exhibit favorable anti-metastasis effects in breast cancer-bearing nude mice. Hence, S/C-pW-LPNs are promising oral drug nanocarriers that inhibit breast cancer lung metastasis.